Generation of Mutant Pigs by Direct Pronuclear Microinjection of CRISPR/Cas9 Plasmid Vectors - Chin-kai Chuang; Ching-Fu Tu; Chien-Hong Chen (Bio-Protocol, 2017)
A set of Cas9 and single guide CRISPR RNA expression vectors was constructed. Only a very simple procedure was needed to prepare specific single-guide RNA expression vectors with high target accuracy. Since the de novo zygotic transcription had been detected in mouse embryo at the 1-cell stage, the plasmid DNA vectors encoding Cas9 and GGTA1 gene specific single-guide RNAs were micro-injected into zygotic pronuclei to confirm such phenomenon in 1-cell pig embryo. Our results demonstrated that mutations caused by these CRISPR/Cas9 plasmids occurred before and at the 2-cell stage of pig embryos, indicating that besides the cytoplasmic microinjection of in vitro transcribed RNA, the pronuclear microinjection of CRISPR/Cas9 DNA vectors provided an efficient solution to generate gene-knockout pig.